Rare genotype del2,3/2184insA in a cystic fibrosis patient. - Lech Chyczewski; Łukasz Minarowski; Danuta Kowalczuk; Maciej Kaczmarski; Oksana Kowalczuk; Alina Minarowska (Folia Histochemica et Cytobiologica, 2007)
In this paper we present an interesting case of cystic fibrosis patient with rare genotype de12,3/2184insA and atypical clinical image including: mild symptoms in an early phase of disease, quick progress of lung disease, complicated with pneumothorax after Bordetella pertussis infection and very good response to systemic and inhaled steroid therapy.